Manajemen Sarana dan Prasarana dalam Pendidikan Anak Usia Dini: Studi tentang Perencanaan, Pengadaan, Pengelolaan, Inventarisasi dan Perawatan - Ulfitika Putri; Andarista Kirana Putri; Mauiza Mauiza; Septiani Agustin; Esi Andra Lista; Fahmi Fahmi (Intitut Agama Islam Nasional Laa Roiba Bogor, 2026)
This research aims to examine the management of facilities and infrastructure in Early Childhood Education (PAUD) which includes planning, procurement, management, inventory, and maintenance. The method used is a literature review by analyzing three relevant scientific journals in the 2021–2026 range. Data is collected through a process of identification, selection, and analysis of literature related to the research topic. The data analysis technique uses a qualitative descriptive approach with a synthesis method to combine various findings of previous research. The results of the study show that facilities and infrastructure management has an important role in improving the quality of learning and supporting early childhood development. Effective management must be carried out systematically through the stages of needs-based planning, efficient procurement, optimal management, orderly inventory, and continuous maintenance. In addition, the success of facilities and infrastructure management is also influenced by the competency factors of educators, budget availability, and support from various parties. However, there are still obstacles in its implementation, such as limited resources and not optimal management in several PAUD institutions. The conclusion of this study emphasizes that integrated and sustainable management of facilities and infrastructure is a strategic factor in improving the quality of early childhood education. Therefore, more systematic and collaborative management is needed so that facilities and infrastructure can be used optimally to support the learning process.